Enteric-coated and highly standardized cranberry extract reduces antibiotic and nonsteroidal anti-inflammatory drug use for urinary tract infections during radiotherapy for prostate carcinoma - Bonetta A; Roviello G; Generali D; Zanotti L; Cappelletti MR; Pacifico C; Di Pierro F (Research and Reports in Urology, 2017)
Alberto Bonetta,1 Giandomenico Roviello,2,3 Daniele Generali,3,4 Laura Zanotti,3 Maria Rosa Cappelletti,3 Chiara Pacifico,5 Francesco Di Pierro6 1Oncological Radiotherapy Operative Unit, ASST, Cremona, 2Department of Molecular and Translational Medicine, University of Brescia, Brescia, 3Molecular Therapy and Pharmacogenomics Unit, ASST, Cremona, 4Department of Medical, Surgery and Health Sciences, University of Trieste, Trieste, 5Department of Medical, Surgical and Neurological Sciences, University Hospital of Siena, Siena, 6Velleja Research Scientific Department, Milan, Italy Introduction: Worldwide, bacterial resistance to antibiotic therapy is a major concern for the medical community. Antibiotic resistance mainly affects Gram-negative bacteria that are an important cause of lower urinary tract infections (LUTIs). Pelvic irradiation for prostate cancer is a risk factor for LUTIs. Cranberry extract is reported to reduce the incidence of LUTIs. The prophylactic role of an enteric-coated, highly standardized cranberry extract (VO370®) in reducing LUTI episodes, urinary discomfort, and nonsteroidal anti-inflammatory drug (NSAID) and antibiotic use during radiotherapy for prostate carcinoma was evaluated. Methods: A total of 924 patients with prostate carcinoma treated by radiotherapy to the prostatic and pelvic areas were randomized to receive (n=489) or not (n=435) the enteric-coated, highly standardized cranberry extract for 6–7 weeks concurrently with irradiation. Outcomes were analyzed by using Mann–Whitney U test and Pearson’s X2 test. Primary endpoint was the number of patients with LUTI; secondary endpoints were incidence of recurrence, days of treatment with antibiotics and number of subjects treated with NSAIDs, and incidence of dysuria. Results: The treatment was very well tolerated, and there were no serious side effects. All enrolled patients completed the study. Urinary infections were detected in 53 of the 489 patients (10.8%) treated with enteric-coated, highly standardized cranberry extract, while 107 of the 435 patients (24.6%) in the control group developed LUTIs (p=0.0001). A clear and significant reduction in urinary discomfort of ~50% was seen in treated subjects. The treatment also resulted in ~50% reduction in the use of anti-inflammatory drugs and antibiotics. Conclusion: The enteric-coated, highly standardized cranberry extract could be used as a prophylactic to reduce the incidence of LUTIs and decrease antibiotic therapy in patients receiving pelvic irradiation for prostate cancer. Keywords: antibiotic-resistance, PAC-A, Vaccinium macrocarpon, UTI, E. coli, botanicals